An efficient continuous flow process for the synthesis of a non-conventional mixture of fructooligosaccharides. (1st January 2016) - Zambelli, Paolo; Tamborini, Lucia; Cazzamalli, Samuele; Pinto, Andrea; Arioli, Stefania; Balzaretti, Silvia; Plou, Francisco J.; Fernandez-Arrojo, Lucia; Molinari, Francesco; Conti, Paola; Romano, Diego
Highlights: A sustainable continuous process for fructooligosaccharide production was developed. The process was set up in a flow chemistry reactor. An immobilized whole cells-packed bed reactor was used. Blastose was isolated and biologically tested. Blastose is able to promote the growth of probiotic strains. Abstract: A sustainable and scalable process for the production of a new mixture of fructooligosaccharides (FOS) was developed using a continuous-flow approach based on an immobilized whole cells-packed bed reactor. The technological transfer from a classical batch system to an innovative flow environment allowed a significant improvement of the productivity. Moreover, the stability of this production system was ascertained by up to 7 days of continuous working. These results suggest the suitability of the proposed method for a large-scale production of the desired FOS mixture, in view of a foreseeable use as a novel prebiotic preparation.